Single mothers as 'imperfect-resilient' subjects and their entrepreneurial narratives on TikTok. - Ntalla, Irida (Continuum: Journal of Media & Cultural Studies, 2026)
This paper examines how self-identified single mothers on TikTok navigate maternal and entrepreneurial identities and aims to monetize their lived experiences by focusing on the content tagged with #singlemomentrepreneur. Drawing from a thematic content analysis of 50 selected TikTok videos, the study explores how this diverse group leverages platform affordances and strategies to reframe stigmatized experiences and views of dependency into aspirational stories of financial independence. The analysis uses McRobbie's perfect–imperfect–resilient (p–i–r) dispositif as a conceptual framework to discuss creators' digital narratives of 'imperfect–resilient' motherhood that frame them as resilient subjects situated within the spaces of the neoliberal ideal of a self-sufficient, self-managing mumpreneur. The findings show three main themes on how these creators present themselves: the sole breadwinner identity as a vital narrative of the single mother entrepreneur, intersectional narratives of resilience through struggle and success and resilience as an educational capital for the single mother community on TikTok. This paper extends scholarship on the mediation of maternal identities and their entrepreneurial labour within TikTok's digital economy as creators negotiate motherhood and work, platform affordances and visibility and neoliberal discourses of resilience.